Evaluation of the impacts of photodynamic therapy on the prognosis of patients with hrHPV infection based on BTNL8 expression - Lv, Hongqing; Lou, Shuai; Zhang, Lin; Cui, Dawei; Li, Yao; Yang, Ying; Chen, Meilan; Chen, Pan (Frontiers in Oncology, 2023)
Objective: To evaluate the prognostic value of Butyrophilin-like protein 8 (BTNL8) expression in high-risk HPV (hrHPV) infection treated with photodynamic therapy. Methods: A totally 93 patients with hrHPV infection were enrolled as research study subjects, along with 69 healthy women who served as controls. Serum samples were obtained from each participant , and BTNL8 levels were quantified. The patients were divided into high- and low-expression groups (n=45 and n=48, respectively), and both groups underwent photodynamic therapy. We recorded the following data: BTNL8 expression pre-treatment and at 3/6 months post-treatment, HPV negative conversion ratio, regression rate of low-grade squamous intraepithelial lesions (LSIL), incidence of adverse reactions, complication rate, serum inflammatory factors, persistence of HPV positivity, LSIL residue or recurrence, and incidence of high-grade cervical intraepithelial lesions (HCIL). Results: Patients with HPV infection exhibited higher BTNL8 expression than healthy individuals. Compared to the low-expression group, the high-expression group showed increased HPV negative conversion ratios, LSIL regression rates, and levels of IL-17 and IL-23. This group also demonstrated decreased total complication rate, HPV positivity persistence, LSIL residue or recurrence, and IL-10 levels. Additionally, there was no significant difference between the two groups in terms of the number of adverse reactions and case with LSIL residue/recurrence. Conclusion: Serum BTNL8 expression may serve as a valuable tool for early screening and prognosis monitoring of patients with hrHPV infection.